Efficacy and Safety of Pramipexole Sustained Release versus Immediate Release Formulation for Nocturnal Symptoms in Chinese Patients with Advanced Parkinson’s Disease: A Pilot Study - Haiyan Zhou; Shuhua Li; Hongmei Yu; Shenggang Sun; Xinhua Wan; Xiaodong Zhu; Chun-Feng Liu; Ling Chen; Wei Xiang; Yaqing Sun; Haibo Chen; Shengdi Chen (Parkinson's Disease)
Objective. To explore the efficacy and safety of pramipexole sustained release (SR) versus pramipexole immediate release (IR) in treating nocturnal symptoms in levodopa-treated Chinese patients with advanced Parkinson’s disease (PD) and sleep disturbances. Method. SUSTAIN was an open-label, randomised, active-controlled parallel group exploratory pilot study (NCT03521635). A total of 98 patients were randomly allocated (1 : 1) to either pramipexole SR (n = 49) or pramipexole IR (n = 49) groups. The primary endpoint was a change from baseline in PD Sleep Scale 2nd version (PDSS-2) total score at 18 weeks. A reduction in score represents improvement. Secondary endpoints included Nocturnal Hypokinesia Questionnaire, Scales for Outcomes in PD Sleep Scale, Early Morning Off (EMO), Epworth Sleepiness Scale, PD Questionnaire-8, and responder rates as measured by PDSS-2 total score (<18), EMO scores (≥1 point change), Clinical Global Impression Improvement scale, and Patient Global Impression-Improvement scale. Other endpoints included motor complications (MDS-UPDRS part IV) score. Adverse events were evaluated for each group. Results. The mean pramipexole dose for both groups was 1.5 mg/day at week 18, and the mean changes in PDSS-2 total score for pramipexole SR and IR were –13.7 (95% CI –16.0 to –11.4) and –14.4 (–16.8 to –12.0) (difference of 0.7; p=0.688). Change from baseline for both groups achieved the minimal clinical important difference threshold (MCID = –3.44). No significant difference was observed in change from baseline for other measures of sleep-related disturbances or responder rates. For motor complications, a greater improvement in MDS-UPDRS part IV score was observed in pramipexole SR over IR (–3.4 vs –2.3; treatment group difference: –1.1; p=0.036). Both groups had comparable safety profiles. Conclusion. In Chinese patients with advanced PD and sleep disturbances, pramipexole SR and IR have similar benefits in the treatment of nocturnal symptoms and safety, and an improvement from baseline in nocturnal symptoms was observed regardless of pramipexole formulation.